(untitled) (Bangladesh Journal of Medicine, 2021)
Tuberous sclerosis complex is an unusual neurocutaneous syndrome with autosomal-dominant inheritance. It is characterized by the development of benign tumors involving the brain, skin, retina, heart, kidneys, lungs, and liver. The classic triad of clinical features comprises learning disability, epilepsy and skin lesions but there is marked heterogeneity in clinical features. Here, we present a case report of a 17-old-year male with characteristic clinical and radiological features of tuberous sclerosis complex. Bangladesh J Medicine July 2022; 33(1) : 99-103